A PERANCANGAN SISTEM KENDALI KENDARAAN BERMOTOR JARAK JAUH MENGGUNAKAN NodeMCU ESP8266 - Choresy Michael G. Butar-butar; Yusran Timur Samuel (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2019)
Turning on a vehicle from a distance is an obstacle for the owners. This happens if he travels far and no one can turn on the vehicle. For this reason, the authors conduct a study to utilize IoT technology (internet of things) that can turn off and turn on a vehicle remotely. By using ESP8266 NodeMCU which is connected with 2 relays and 2 sensor that is a SW420 vibration sensor and a tilt sensor the SW460D can produce a hardware configuration to control the vehicles from a distance. As an interface controller, one application has been programmed using the Android-based Blynk application. This design has been tested on a motorcycle for a month, from March 1 to April 1. the result shows that it works, and it is always succeeded to control the motorcycle from a far if the system gets a wifi signal with an internet connection. Keywords: IoT, NodeMCU, SW420 vibration sensor, SW460D tilt sensor